Cartography of Emergency Department Visits for Asthma – Targeting High-Morbidity Populations. Issue 6 (3rd September 2004) - Lajoie, Pierre; Laberge, Andrée; Lebel, Germain; Boulet, Louis-Philippe; Demers, Marie; Mercier, Pierre; Gagnon, Marie-France
Abstract : BACKGROUND: Asthma education should be offered with priority to populations with the highest asthma-related morbidity. In the present study, the aim was to identify populations with high-morbidity for asthma from the Quebec Health Insurance Board Registry, a large administrative database, to help the Quebec Asthma and Chronic Obstructive Pulmonary Disease Network target its interventions. METHODS: All emergency department (ED) visits for asthma were analyzed over a one-year period, considering individual and medical variables. Age- and sex-adjusted rates, as well as standardized rate ratios related to the overall Quebec rate, among persons zero to four years of age and five to 44 years of age were determined for 15 regions and 163 areas served by Centres Locaux de Services Communautaires (CLSC). The areas with rates 50% to 300% higher (P<0.01) than the provincial rate were defined as high-morbidity areas. Maps of all CLSC areas were generated for the above parameters. RESULTS: There were 102, 551 ED visits recorded for asthma, of which more than 40% were revisits. Twenty-one CLSCs and 32 CLSCs were high-morbidity areas for the zero to four years age group and five to 44 years age group, respectively. For the most part, the high-morbidity areas were located in the south-central region of Quebec. Only 47% of asthmatic patients seen in ED had also seen a physician in ambulatory care. CONCLUSION: The data suggest that a significant portion of the population seeking care at the ED is undiagnosed and undertreated. A map of high-morbidity areas that could help target interventions to improve asthma care and outcomes is proposed.